Birth of an order: Comprehensive molecular phylogenetic study excludes Herpomyces (Fungi, Laboulbeniomycetes) from Laboulbeniales - Haelewaters, Danny; Pfliegler, Walter P; Gorczak, Michał; Pfister, Donald H (Molecular phylogenetics and evolution, 2019)
The class Laboulbeniomycetes comprises biotrophic parasites associated with arthropods and fungi. Two orders are currently recognized, Pyxidiophorales and Laboulbeniales. Herpomyces is an isolated genus of Laboulbeniales, with species that exclusively parasitize cockroaches (Blattodea). Here, we evaluate 39 taxa of Laboulbeniomycetes with a three-locus phylogeny (nrSSU, ITS, nrLSU) and propose a new order in this class. Herpomycetales accommodates a single genus, Herpomyces, with currently 26 species, one of which is described here based on morphological and molecular data. Herpomyces shelfordellae is found on Shelfordella lateralis cockroaches from Hungary, Poland, and the USA. We also build on the six-locus dataset from the Ascomycota Tree of Life paper (Schoch and colleagues, 2009) to confirm that Laboulbeniomycetes and Sordariomycetes are sister classes, and we apply laboulbeniomyceta as a rankless taxon for the now well-resolved node that describes the most recent common ancestor of both classes.
Keywords: nukleotidy; Hungary; Phylogeny; švábi; Ascomycota; Maďarsko; druhová specificita; Divergence times; Laboulbeniomycetes; Animals; Nucleotides; Species Specificity; zvířata; fylogeneze; Ectoparasitic fungi; Cockroaches